Functionally Important Amino Acid Residues in the Transient Receptor Potential Vanilloid 1 (TRPV1) Ion Channel - An Overview of the Current Mutational Data. (22nd June 2013) - Winter, Zoltán; Buhala, Andrea; Ötvös, Ferenc; Jósvay, Katalin; Vizler, Csaba; Dombi, György; Szakonyi, Gerda; Oláh, Zoltán
This review aims to create an overview of the currently available results of site-directed mutagenesis studies on transient receptor potential vanilloid type 1 (TRPV1) receptor. Systematization of the vast number of data on the functionally important amino acid mutations of TRPV1 may provide a clearer picture of this field, and may promote a better understanding of the relationship between the structure and function of TRPV1. The review summarizes information on 112 unique mutated sites along the TRPV1, exchanged to multiple different residues in many cases. These mutations influence the effect or binding of different agonists, antagonists, and channel blockers, alter the responsiveness to heat, acid, and voltage dependence, affect the channel pore characteristics, and influence the regulation of the receptor function by phosphorylation, glycosylation, calmodulin, PIP2, ATP, and lipid binding. The main goal of this paper is to publish the above mentioned data in a form that facilitates in silico molecular modelling of the receptor by promoting easier establishment of boundary conditions. The better understanding of the structure-function relationship of TRPV1 may promote discovery of new, promising, more effective and safe drugs for treatment of neurogenic inflammation and pain-related diseases and may offer new opportunities for therapeutic interventions.